The Value Of 3 Tesla Magnetic Resonance Imaging In Assessment Of Clinically Diagnosed Temporomandibular Joint Disorders - Hammod, Zeinab G; Al-Nakib, Lamia H (Journal of Baghdad College of Dentistry, 2017)
Background: Temporomandibular joint disorder (TMD) is a general term that describe a wide variety of conditions that include myogenic pain, internalderangement, arthritic problem, ankylosis of the joint and growth disorders. The aims of study was to evaluate the value of 3 Tesla magnetic resonance imaging in assessment of articular disc position and configuration in patients with temporomandibular joint disorders and to evaluate the correlations of these MRI findings with the clinical signs and symptoms. Materials and methods: A total forty six (30 study and 16 control) participants aged between18 and 49 years, were examined according to Helkimo anamnestic index (questionnaire for anamnesis) and clinical dysfunction index scoring criteria which include clinical examinations of the range of mandibular mobility, impaired TMJ function, muscle pain ,TMJ pain and pain during mandibular movement. Results: There is statistically high significant difference between Helkimo anamnestic and clinical dysfunction indices in the cases group (with temporomandibular joint disorders) and controls group with MRI findings of disc position and disc configuration, that as the severity of indices increased, there were progression of disc displacement and disc deformity score and shows positive association expressed by significant probability (p) value. Conclusion: There is a significant correlation between Helkimos’ anamnestic and clinical dysfunction indices and MRI findings in patients with internal derangement of temporomandibular joint.